Mouse DC-SIGN/CD209a as Target for Antigen Delivery and Adaptive Immunity - Schetters, Sjoerd T. T.; Kruijssen, Laura J. W.; Crommentuijn, Matheus H. W.; Kalay, Hakan; Ochando, Jordi; den Haan, Joke M. M.; Garcia-Vallejo, Juan J.; van Kooyk, Yvette (Frontiers in Immunology, 2018)
The efficacy of vaccination studies aimed at targeting antigens to human DC-SIGN have been notoriously difficult to study in vivo, as eight DC-SIGN homologues have been described in mice. CD209a/SIGNR5 has been coined as the murine DC-SIGN (mDC-SIGN) ortholog, based on its expression and location in the genome. Nonetheless, which properties of human DC-SIGN are covered by mDC-SIGN is poorly investigated. One of the most important functions of DC-SIGN is the induction of adaptive immunity. As such, the aim of this study is to determine the capability of mDC-SIGN to induce adaptive immune responses. Here, we show that mDC-SIGN is expressed on GM-CSF cultured bone marrow-derived dendritic cells and macrophages. However, unlike hDC-SIGN, mDC-SIGN is an internalizing receptor which quickly resurfaces after internalisation. Binding of OVA-coupled anti-mDC-SIGN antibody by BMDCs leads to quick internalization, processing and presentation to antigen-specific CD8+ and CD4+ T cells, which can be boosted using the TLR4 ligand, MPLA. In the homeostatic condition, mDC-SIGN is mostly expressed on myeloid cells in the skin and spleen. A subcutaneous injection of fluorescently-labeled anti-mDC-SIGN reveals specific targeting to mDC-SIGN+ skin dendritic cells and monocyte-derived dendritic cells in situ. A subcutaneous vaccination strategy containing OVA-coupled anti-mDC-SIGN antibody generated antigen-specific polyfunctional CD8+ T cell and CD4+ T cell responses and a strong isotype-switched OVA-specific antibody response in vivo. We conclude that mDC-SIGN shows partly overlapping similarities to hDC-SIGN and that targeting mDC-SIGN provides a valuable approach to investigate the immunological function of DC-SIGN in vivo.